A critical review on life-cycle assessment and exergy analysis of Enomoto bio-gasoline production. (15th December 2022) - Shearian Sattari, Mojdeh; Ghobadian, Barat; Gorjian, Shiva
Abstract: Considering algae as a diversified source of various chemicals, the purifying process, and treatment pathways, also deciding on algal strains sound vital rather than coming across. To attain low emission fuels from Enomoto, fast catalytic pyrolysis reactions could provide anti-knock properties of gasoline blends. The whole issue is under investigation by lifecycle assessment (LCA) and exergy analysis within this scope. There has been no "Mixed Review Study" for these analyses on effective SATBA 1 's goals and Enomoto biogasoline, hitherto. In this study, the consequence of carbon cycle stabilization has been pursued from the beginning of the supply chain, production (electrical energy with the highest contribution), and distribution of Enomoto biogasoline, and the share of total emissions reached 14.14 kgCO2 /kg fuel. In this research work, LCA outcome was performed with energy balance to optimize the dead states of various exergy losses and compared it with the values of a base reference by the Greenhouse gases, Regulated Emissions, and Energy use in Transportation (GREET) method. For this purpose, for every 838 kJ/L of Enomoto oil, 128834.824 MJ/day of chemical exergy was produced in the system, and the share of physical exergy input at 94355.16 MJ/day, which indicates high efficiency of the process. There was an inextricable correlation between Neat Energy Ratio (NER) 2.27, 80.3% efficiency, and low carbon dioxide (CO2 ) emissions with Energy Consumption Ratio (ECR) approximately 0.001. Also, improving the process and reducing the loss of exergy, i.e. destructive exergy equivalent to 973, 879 kJ/day can be significantly improved by removing the heat exchanger and replacing the reactor and condenser type. As a result, it has proved that this process is economically feasible for 1250 L per day of Enomoto biogasoline production with an annual depreciation of about $18, 000 at the MFSP, which is about 24.7% less than the free-rate price of gasoline. This is important despite the increase in the global price of gasoline in the next decade at $1.18; even the NPV will reach $5.2 million annually and a return on investment within 5 years of launching this valuable pilot.